2009
DOI: 10.1158/1541-7786.mcr-08-0558
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Is a Key Nonredundant Mediator of Transforming Growth Factor β Signaling in Nme Mouse Mammary Epithelial Cells

Abstract: Smad2 and Smad3 are intracellular mediators of transforming growth factor β (TGFβ) signaling that share various biochemical properties, but data emerging from functional analyses in several cell types indicate that these two Smad proteins may convey distinct cellular responses. Therefore, we have investigated the individual roles of Smad2 and Smad3 in mediating the cytostatic and proapoptotic effects of TGFβ as well as their function in epithelial-to-mesenchymal transition. For this purpose, we transiently dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…Furthermore, in vitro studies have shown that Smad2 and Smad3 have unique functions in mammary epithelium and oncogenesis, in which Smad3 and not Smad2 is critical to inducing TGFβ-mediated apoptosis, cell cycle arrest and EMT. 18,19 …”
Section: Tgfβ and Smad Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in vitro studies have shown that Smad2 and Smad3 have unique functions in mammary epithelium and oncogenesis, in which Smad3 and not Smad2 is critical to inducing TGFβ-mediated apoptosis, cell cycle arrest and EMT. 18,19 …”
Section: Tgfβ and Smad Signalingmentioning
confidence: 99%
“…As stated, TGFβ can stimulate tumor progression and metastasis by inducing EMT 72,73 in a process that is Smad3-dependent. 19 During EMT, cells lose their epithelial characteristics, including cell adhesion and polarity, and acquire a mesenchymal morphology and the ability to migrate. During this process, cells downregulate the expression of epithelial markers and upregulate the expression of mesenchymal markers.…”
Section: Role Of Smad3 In Pro-metastatic Eventsmentioning
confidence: 99%
“…In the 4T1 and the MDA-MB-231 tumor models, systemic administration of a soluble TbRII protein or dominant negative TbRII overexpression, respectively, displayed anti-metastatic effects (Yin et al, 1999;Muraoka et al, 2002). Several studies have provided evidence that Smad2 and Smad3 have different transcriptional functions and profiling studies have revealed distinct target genes for Smad2 and Smad3 (Kretschmer et al, 2003;LaGamba et al, 2005;Dzwonek et al, 2009). In addition, although mice deficient in Smad2 are embryonic lethal, Smad3-deficient mice are viable (Weinstein et al, 1998;Ashcroft et al, 1999;Yang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure was performed in hippocampal or cortical extracts from rats that were sacrificed on E18 or P3-P60, or extracts from cell cultures as described previously (Dzwonek et al, 2009). The following antibodies were used: sheep anti-CD44 (R&D Systems), rabbit anti-GFP (MBL International), chicken anti-b-galactosidase (Abcam), mouse anti-GAPDH (Millipore) and anti-Src (Cell Signaling).…”
Section: Western Blottingmentioning
confidence: 99%